2016
DOI: 10.1021/acs.jpcc.6b00815
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production via Hydrazine Decomposition on Model Platinum–Nickel Nanocatalyst with a Single (111) Facet

Abstract: Model octahedral Pt–Ni/C nanocatalyst with different particle composition (0.5 ≤ Pt/Ni ≤ 4) was prepared and researched in hydrazine decomposition for hydrogen generation. The experiments discovered dependency of the catalyst activity, selectivity, durability, and stability on both the particle composition and morphology, with the octahedral PtNi/C being found to be the most active and 100% selective, with superior durability and stability. Mechanistic studies and discussions on the reaction mechanism and kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 70 publications
(97 reference statements)
1
14
0
Order By: Relevance
“…In the past decade, significant progresses has been made in developing active and selective catalysts for promoting H 2 generation from N 2 H 4 ⋅ H 2 O. It was found that alloying Ni with noble metals, such as Pt, Ir, Rh, or Pd, resulted in remarkable improvement to the catalytic activity and H 2 selectivity . In particular, immobilized Ni−Pt or Ni−Ir alloy nanoparticles on alkaline metal oxides (e.g., CeO 2 , La 2 O 3 ) enabled the complete decomposition of N 2 H 4 ⋅ H 2 O at mild temperatures with 100 % H 2 selectivity .…”
Section: Introductionmentioning
confidence: 75%
“…In the past decade, significant progresses has been made in developing active and selective catalysts for promoting H 2 generation from N 2 H 4 ⋅ H 2 O. It was found that alloying Ni with noble metals, such as Pt, Ir, Rh, or Pd, resulted in remarkable improvement to the catalytic activity and H 2 selectivity . In particular, immobilized Ni−Pt or Ni−Ir alloy nanoparticles on alkaline metal oxides (e.g., CeO 2 , La 2 O 3 ) enabled the complete decomposition of N 2 H 4 ⋅ H 2 O at mild temperatures with 100 % H 2 selectivity .…”
Section: Introductionmentioning
confidence: 75%
“…The existence of Ni and Pd metals in an alloy state is a key factor behind the observed high catalytic performance. 46 The monometallic Pd/rGO and Ni/rGO nanocatalysts show poor catalytic activity for the hydrogen generation from hydrazine, while the presence of both metals with inter-metallic Ni-Pd bonding on the catalyst active centres is vital for the activation of bonds in hydrazine for hydrogen generation. The rGO supports are also important, because they prevent the aggregation of Pd 3 Ni NPs during the dehydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…284 The catalytic activity of hydrogen evolution from hydrous hydrazine was further improved by using well-dispersed rhodium-nickel nanoparticles grown on graphene. 285 Noble-metal-modified Ni catalysts, in particular Rh-Ni, 285,287,288 Pt-Ni, [289][290][291][292][293][294][295][296][297] and Ir-Ni, [298][299][300] Ni-Pd 301 were most efficient for the selective decomposition of hydrous hydrazine due to the prominent alloy synergy effect. Noble-metal-free NiFeMo nanoparticles (Ni 0.6 Fe 0.4 Mo NPs) without any surfactant or support have been facilely synthesized and applied as an efficient catalyst for the rapid and complete decomposition of hydrous hydrazine to hydrogen and nitrogen (Equation 40) at a mild temperature.…”
Section: Direct Methanol Fuel Cellmentioning
confidence: 99%